Effect of local ozone therapy on inflammatory markers in experimental ulcerative colitis - E. V. Davydova; M. V. Osikov; N. V. Kaygorodtseva (Бюллетень сибирской медицины, 2022)
Aim. To evaluate the effect of rectal insufflations of medical ozone on markers of inflammation in experimental ulcerative colitis.Materials and methods. The experimental study was performed in vivo on 49 white, sexually mature male Wistar rats weighing 250 ± 15 g. The model of ulcerative colitis was reproduced using two-stage oxazolone administration (Sigma-Aldrich, USA). A group of animals received rectal insufflations of medical ozone at a dose of 1.0 mg / l once a day in the volume of 10 ml of ozone / oxygen mixture. The cycle of insufflations lasted 10 days. The ozone / oxygen mixture was obtained using an automated ozone therapy device with an ozone destructor UOTA-60-01“Medozon” (Medozon LLC, Moscow, Russian Federation). According to the disease activity index (DAI) score, the disease activity index was evaluated. The intensity of neutrophil phagocytosis in the blood was detected using polystyrene latex particles. The ability of neutrophils to reduce nitroblue tetrazolium (NBT) was determined using spontaneous and induced NBT tests. The interleukin-17 (IL-17) concentration in the serum was determined by enzyme-linked immunosorbent assay (ELISA) using a test system for rats manufactured by Bender MedSystems (Austria).Results. Under the conditions of ozone therapy by rectal insufflations in experimental ulcerative colitis, we demonstrated improvement in the clinical presentation of the disease, intensity of phagocytosis, phagocytic index, and spontaneous and induced ability of neutrophils to reduce NBT with normalization of the functional reserve of cells and the level of proinflammatory IL-17 on day 6 of the experiment.Conclusion. The results obtained allow to verify pronounced anti-inflammatory and immunomodulatory effects of ozone and consider it as one of the most relevant treatment strategies for inflammatory bowel diseases.